Kontradiksi Pertumbuhan Ekonomi Dan Ketimpangan Pendapatan: Kasus Anomalistik Dua Provinsi Berbasis Pesisir - Ridwan, Mochamad (Convergence: The Journal of Economic Development, 2022)
The contradictory economic conjuncture of economic growth and income inequality began with the continuous economic recession and was strengthened by the pressure of the COVID-19 pandemic. The aim of this research is to reveal and analyze the causes of the problem of economic contraction and income inequality in Bengkulu and Kepulauan Riau Provinces. The type of data collected only comes from secondary data, namely from the Indonesian Central Bureau of Statistics (BPS), which is analyzed using statistical analysis and descriptive analysis methods. The research results showed that the trend of economic growth and economic inequality in the two provinces (Bengkulu and Kepulauan Riau) are both decreasing. The bad influence (backwash effect) in the form of a global economic recession and the Covid-19 pandemic case (2019–2020) is considered to be the cause of economic contraction in the form of a decline in economic growth which is extreeme/minus (-0.02 in Bengkulu Province and -3.80 in Kepulauan Riau Province). The trend of income inequality (measured by the Gini index) which is decreasing from year to year is considered a form of contradiction (anomaly) because it is considered to be at odds with the decline in economic growth at the same time. Keywords: Economic contraction, Economic growth, Income inequality, Economic recession